Oral lichenoid lesion simultaneously associated with Castleman's disease and papillary thyroid carcinoma: a rare case report - Jiaying Zhou; Rui Zhou; Pingping Tan; Bin Cheng; Liwei Ma; Tong Wu (BMC, 2022)
Abstract Background Oral lichenoid lesion (OLL) is a term used to describe oral lesions that have clinical and/or histopathological features similar to oral lichen planus (OLP), but it is thought to be caused by specific triggers or systemic conditions and presents higher malignant transformation rate than OLP. To date, OLL simultaneously complicated with Castleman's disease (CD) and papillary thyroid carcinoma (PTC) has not been reported. Reporting from such disorders is crucial to avoid misdiagnosis and help in timely intervention. Case presentation We report a rare case of a 39-year-old female with extensive ulcerated lesions on the oral mucosa, diagnosed as OLL by histopathology. Routine oral treatment was scheduled to control the OLL, while the oral lesions remained unhealed. Computed tomography examination was performed after the oral treatment and revealed thyroid and mediastinal masses, which were then surgically removed and pathologically diagnosed as PTC and CD, respectively. Two months after complete excision of the neoplasms, the oral lesions showed obvious alleviation. With subsequent treatment for oral lesions, the patient's OLL healed. Conclusions This is the first reported OLL case simultaneously associated with CD and PTC. This case reminds us to focus on the underlying etiologies of OLL and the multidisciplinary collaboration for oral lesions associated with systemic diseases.